Primate adaptation and evolution - Fleagle, John G. 1948- (Elsevier/Academic Press, 2013)
For many years John Fleagle's text on the adaptation and evolution of primates and early hominoid fossils was the the text of choice for teachers and research workers alike. Now, as the only such work in print, this new edition brings this coverage up to date with the latest fossil finds and most current research. The book retains its grounding in the extant primate groups as the best way to understand the fossil trail and the evolution of these modern forms. But this coverage is now streamlined, making reference to the many new and excellent books on living primate ecology and adaptation - a field that has burgeoned since the first edition of Primate Adaptation and Evolution. By drawing out the key features of the extant families and referring to more detailed texts, Fleagle sets the scene and also creates space for a thorough updating of the exciting developments in primate palaeontology - and the reconstruction through early hominid species - of our own human origins. Illustrated with many of the classic pictures from earlier editions - and whole new suite of illustrations, revised evolutionary trees and tables - this book remains the indispensible text on this fascinating subject. Long-awaited revision of the standard student text on primate evolutionFull coverage of newly discovered fossils and the latest taxonomyOver 200 new illustrations and revised evolutionary trees